Enhancing Critical Thinking Skills in Nursing Higher Education in Preparation for the Industrial Revolution 4.0 - Bangun, Argi Virgona; Pragholapati, Andria (KnE Life Sciences, 2021)
Nursing higher education will challenge the dynamics of the work environment in the Industrial Revolution Era 4.0 and they will compete with digital technology. Critical thinking skills as one of the basic competencies must support higher education in preparation for the industrial revolution 4.0. Exploring thinking skills makes nursing students will be trained in their punishment and analysis skills according to their knowledge. Critical thinking skills not only guide students to develop continuing skills, but also help nursing students to be motivated to create innovation in college. The aims of this review is to learn the critical skills needed in higher education to prepare for the industrial revolution 4.0 based on literature understanding. There are 6 (six) important things about Critical Thinking in nursing education in the Industrial Revolution Era 4.0, namely Definition of Critical Thinking, Why do we need to focus on critical thinking in higher education, Why is critical thinking needed in industry 4.0 preparation, Industry Innovation 4.0 and human potential to overcome environmental problems, Critical Thinking in Nursing Education, and Educational Strategies for Developing Critical Thinking in Nursing. These critical thinking skills are suitable for equipping students in higher education before they enter different workplaces. Educational strategies in developing critical thinking skills by supporting the use of questions, small group activities, role plays, debates, use of case studies, journals, simulations, puzzles, problem solving and writing assignments. Nursing students who think critically in line with creative thinking and innovation will be useful to survive in the dynamics of the industrial revolution 4.0 and beyond in the world of the future. Keywords: Critical Thinking, Nursing Higher Education, Industrial Revolution 4.0